Evaluation of optimum dietary lipid levels for juvenile parrot fish (Oplegnathus fasciatus) through 22 week feeding trial - Gunho Eom; Kokila Sanjeewani; Daehyun Ko; Yeonji Lee; Sung-Sam Kim; Kyeong-Jun Lee (Fisheries and Aquatic Sciences)
A 22 weeks of feeding trial was carried out to establish the optimum lipid levels in diet for juvenile parrot fish (Oplegnathus fasciatus). Five diets with 80, 120, 160, 200, and 240 g/kg lipid (L80, L120, L160, L200, and L240, respectively) were prepared supplementing graded levels of squid liver oil. The determined dietary lipid levels were 79, 119, 160, 193, and 228 g/kg for the L80, L120, L160, L200, and L240, respectively. Total 375 juvenile parrot fish (6.35 ± 0.03 g) were distributed into 15 tanks in triplicates and fed their respective diet during the feeding trial. Final body weight and specific growth rate (SGR) of the fish were significantly improved with the increment of dietary lipid up to 160 g/kg. Feed conversion ratio of the fish was significantly decreased with the increment of dietary lipid up to 160 g/kg. Protein efficiency ratio of the fish was significantly higher in the L160, L200, and L240 groups than in the L80, and L120 groups. Lipid efficiency ratio of the fish was significantly decreased with the increasing dietary lipid level. Lipid retention (LR) in the fish was significantly lower in the L160, L200, and L240 groups than in the L80, and L120 groups. Survival of the fish was not significantly different among all the groups. The whole-body protein levels of the L160, and L240 groups were significantly lower than that of the L80 group. The lipid levels of whole-body and liver in the L160, L200, and L240 groups were significantly higher than those of the L80 group. The L200 group showed significantly higher hepatosomatic index than the L80 group. Viscerosomatic index, condition factor and visceral fat level of the fish were significantly increased with the increment of dietary lipid. Our findings suggest that the optimum lipid level of juvenile parrot fish is likely to be 120–153 g/kg diet, by broken-line model based on LR and SGR.